ANALISIS INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Hasan, Hasan (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2011)
The current development of Islamic banking industry in Indonesia is rapidly growing. This article analyzes the Islamic banking industry in Indonesia using Porter’s five-forces competitive industry approach. Each of the power industry are discussed. The conclusion indentifies Islamic banking industry conditions that need to be considered.